How do you spell unfair? : MacNolia Cox and the National Spelling Bee - Weatherford, Carole Boston, 1956-; Morrison, Frank, 1971- (Somerville, Massachusetts : Candlewick Press, 2023)
A true story of determination and groundbreaking achievement follows eighth grade African American spelling champion MacNolia Cox, who left Akron, Ohio, in 1936 to compete in the prestigious National Spelling Bee in Washington, D.C., only to be met with prejudice and discrimination.
Booklist starred, February 2023
Publishers Weekly, January 2023
Kirkus Starred, March 2023
5.3
3-6
840L
Keywords: Cox, MacNolia -- Juvenile literature; African American students -- Biography -- Juvenile literature; Spelling bees -- United States -- Juvenile literature; Race discrimination -- United States -- Juvenile literature; Cox, MacNolia; African American students; Spelling bees; Race discrimination; African Americans -- Biography; Women -- Biography; Biographies; Nonfiction picture books